2021
DOI: 10.1007/s10955-021-02831-0
|View full text |Cite
|
Sign up to set email alerts
|

Contraction: A Unified Perspective of Correlation Decay and Zero-Freeness of 2-Spin Systems

Abstract: We study the connection between the correlation decay property (more precisely, strong spatial mixing) and the zero-freeness of the partition function of 2-spin systems on graphs of bounded degree. We show that for 2-spin systems on an entire family of graphs of a given bounded degree, the contraction property that ensures correlation decay exists for certain real parameters implies the zero-freeness of the partition function and the existence of correlation decay for some corresponding complex neighborhoods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 49 publications
3
17
0
Order By: Relevance
“…Understanding the connection between strong spatial mixing and absence of zeros on families of graphs like G ∆ has recently started to receive attention [20,27,28,36]. In particular in [27,36] it is shown that a standard method for proving strong spatial mixing can be used to prove absence of zeros for partition functions of several models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the connection between strong spatial mixing and absence of zeros on families of graphs like G ∆ has recently started to receive attention [20,27,28,36]. In particular in [27,36] it is shown that a standard method for proving strong spatial mixing can be used to prove absence of zeros for partition functions of several models.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the connection between strong spatial mixing and absence of zeros on families of graphs like G ∆ has recently started to receive attention [20,27,28,36]. In particular in [27,36] it is shown that a standard method for proving strong spatial mixing can be used to prove absence of zeros for partition functions of several models. Very recently, Gamarnik [20] showed that absence of zeros of the partition function implies a weaker form of strong spatial mixing, but his result does not apply to all bounded degree graphs.…”
Section: Introductionmentioning
confidence: 99%
“…And if ( , , ) lies outside this regime, the sampling problem becomes computationally intractable [SS12,GŠV15]. Similar bounds were also achieved by another family of critical algorithms based on polynomial interpolation approach for approximating non-vanishing polynomials [PR19, LSS19,SS20]. A glaring issue with both these families of critical algorithms is the expensive time cost, usually in a form of (log Δ) , which is due to enumerating (log )-sized local structures in these algorithms.…”
mentioning
confidence: 75%
“…In particular, many of the recent advances on the development of approximation algorithms for counting problems have been based on viewing the partition function as a polynomial of the underlying parameters in the complex plane, and using refined interpolation techniques from [1,32] to obtain efficient approximation schemes, even for real values [17,18,27,4,2,28,36,35,34]. The bottleneck of this approach is establishing zero-free regions in the complex plane of the polynomials, which in turn requires an in-depth understanding of the models with complex-valued parameters.…”
Section: Introductionmentioning
confidence: 99%